A study of tendency of deviant behaviour among students in UiTM Kedah / Akram Hakim Ab Rahman and Mohd Amri Othman - Ab Rahman, Akram Hakim; Othman, Mohd Amri (2019)
The aim of this study is to identify the factors that influence the level of deviant behaviour among youth. The study conducted in Universiti Teknologi Mara (UiTM) Kedah. The study was conducted on the student of UiTM Kedah as to represent the youth as student age comply with the youth age definition. Convinience sampling technique was utilized in this research to gather the data from a total of 366 students. The instruments used in this study were adapted from several past studies. The data obtained were analysed based on the objective and hypothesis of the study. Descriptive and percentage analysis were used to determine the frequency and level of deviant behaviour among the secondary school students studied. Frequency and percentage analyses were used to view respondents' background distribution such as gender, home residence and family background. The data were analysed using Statistical Package for the Social Science (SPSS) version 25 software. Descriptive analysis was used to describe the frequency, percentage, mean and standard deviation. Pearson Correlation was used to test the hypothesis of this study. From the finding of the research there was a negative correlation between parental affections and deviant behaviour. While, media was positively correlated with the deviant behaviour.